STRENGTHENING INSTITUTIONAL SYNERGY IN WASTE MANAGEMENT: CHALLENGES AND STRATEGIC SOLUTIONS - Wiranti,; Naswar,; Putri Regita Salsabila Oktaviani,; Irma Idris, (Jurnal Legislatif, 2025)
This study is entitled "Strengthening Institutional Synergy in Waste Management: Challenges and Strategic Solutions". Waste management in Indonesia is experiencing major challenges, such as increasing waste volume, low public awareness, limited infrastructure, and limited regional funding, as well as coordination and synergy between the institutions involved. This study was conducted to determine the role of central and regional institutions in waste management governance in Indonesia and to determine the challenges and strategies that can be applied to improve institutional synergy in sustainable waste management. This study uses a systematic literature review method, namely by the process of placing, obtaining, reading, and evaluating various research literature related to or related to the problem to be studied. The results of this study indicate that problems in managing waste can be overcome through synergy between central and regional institutions. One of the central institutions in this problem is the Ministry of Environment. In carrying out its role, of course, the Ministry of Environment. requires the role and assistance of the regional apparatus as an institution that has the authority to regulate regional affairs.